2017
DOI: 10.1155/2017/3576509
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic Fixed-Bed Gasification of Colombian Coffee Husk Using Air-Steam Blends for Partial Oxidation

Abstract: The increasing energy consumption, mostly supplied by fossil fuels, has motivated the research and development of alternative fuel technologies to decrease the humanity's dependence on fossil fuels, which leads to pollution of natural sources. Small-scale biomass gasification, using air-steam blends for partial oxidation, is a good alternative since biomass is a neutral carbon feedstock for sustainable energy generation. This research presents results obtained from an experimental study on coffee husk (CH) gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This section compares the results of this study to others carried out by the authors, using steam-air mixtures as an oxidizer and the same biomass (Bonilla and Gordillo, 2017). The use of oxygen-mixtures as gasifying agent enhances the temperature along the gasifier, and hence the mole fractions of CO and H 2 in the syngas yield as compared to the use of steam-air-i.e., at SF = 0.4 and ER = 3.2, the CO and H 2 dry basis concentrations were 25 and 27.5%, respectively, for oxygen-steam, whereas these for gasification with air-steam were 12.4 and 12.4%, respectively.…”
Section: Multiple Linear Model For Co and H 2 Concentrationmentioning
confidence: 77%
See 1 more Smart Citation
“…This section compares the results of this study to others carried out by the authors, using steam-air mixtures as an oxidizer and the same biomass (Bonilla and Gordillo, 2017). The use of oxygen-mixtures as gasifying agent enhances the temperature along the gasifier, and hence the mole fractions of CO and H 2 in the syngas yield as compared to the use of steam-air-i.e., at SF = 0.4 and ER = 3.2, the CO and H 2 dry basis concentrations were 25 and 27.5%, respectively, for oxygen-steam, whereas these for gasification with air-steam were 12.4 and 12.4%, respectively.…”
Section: Multiple Linear Model For Co and H 2 Concentrationmentioning
confidence: 77%
“…A secondary oxygen injection of 33% of primary oxygen reduced the tar concentration from 15.78 to 10.24 g/Nm 3 . Bonilla and Gordillo (2017) performed experimental research on autothermal gasification of CH using air-steam blends as gasifying agents. In their research, Equivalence Ratio (ER) and Steam-Fuel Ratio (SF) were the parameters set which ranged 1.53-6.11 and 0.23-0.89, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The development of cutting-edge technologies based on thermochemical processes for the transformation of second-generation feedstock into competitive biofuels has led to study new raw materials [1, 2, 3, 4, 5, 6, 7, 8, 9, 10]. Biomass belongs to this kind of feedstock and previous research have confirmed many advantages on raw material to be converted via pyrolysis [11, 12, 13, 14, 15, 16, 17, 18, 19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Biomass with low calorific value results in poor and unstable combustion whereas biomasses with high ash content cause problems in burners and boilers due to the slag and dirt produced. Complete combustion and gasification of biomass with air have been deeply studied during the last decades [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%